(untitled) (Scientific journal of the Fergana State University, 2024)
This article will focus on the effectiveness of using game-based teaching methods and multimedia tools in improving the reading literacy of younger schoolchildren. The article discusses the methods of using multimedia tools developed by a number of scientists and specialists. The article highlights the results of the study of the problem, the importance of the methods used in the development of students’ skills of concentration, vocabulary replenishment and self-control.